Your World Not Mine: Racialized Women Navigating the Racialized Workplace - Bailey, Monetta (Journal of Critical Race Inquiry, 2026)
This paper uses critical race theory as the theoretical basis for considering the voices of racialized women in professional settings in Alberta and British Columbia, Canada. Using the concept of the racialized social system, I investigate the experiences of racialized women in the workplace, looking at the impact of the intersection of their racial and gender identities. The 24 respondents in this study represented diverse racialized women who spoke about their responses to racial and gendered stereotypes in the workplace. Respondents reported self-monitoring, behaviour-policing, and self-exclusion, resulting in negative impacts on their mental health. The results of the study are presented as composite counter-narratives. I argue that given that the workplace is a significant place where racialization and racism take place, the current movement to remove initiatives to address racism in the workplace, which has happened without the input of racialized women, is causing them harm.